Islam and Terrorism in Political Framing - Wahyu Wiji Utomo (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2022)
Abstract The bombing in Bali on October 12, 2002, the bombing of the WTC in the US on September 11, 2011, and other bombings were international acts. The bombing incident that took place at the international level has opened the eyes of various parties to the dangers of attack. After that, the US and the West joined forces to fight the enemy. What is a problem that often occurs is the accusation of terrorism put forward by Muslims so that Islamic teachings are marginalized and blasphemed by the west. Islam has become a scourge and brings havoc, as a result of terror attacks that have been carried out by people of other religions against Muslims, especially in countries with Muslim minorities. At the same time, framing of Muslims who are attached to terrorism and radicalism is always echoed, from within Islam and from outside Islam though, both in various elements including in the political field. This article seeks to find an understanding of terrorism, which is often framed based on Islamic teachings, whereas actions do not only focus on religious sentiments but actions that come from many more complex aspects. Because if it is not immediately straightened out, the public perception of Islam and terrorism will become a source of disharmony within the religious community and also the state, plus the bad framing of Islam becomes public consumption that is still common to current political interests. Keywords: Islam, Terrorism, Framing, Politics